A viable circulating tumor cell isolation device with high retrieval efficiency using a reversibly deformable membrane barrier. (11th January 2017) - Kim, Yoonji; Bu, Jiyoon; Cho, Young-Ho; Son, Il Tae; Kang, Sung-Bum
Abstract: Circulating tumor cells (CTCs) contain prognostic information of the tumor, since they shed from the primary tumor and invade into the bloodstream. Therefore, the viable isolation is necessary for a consequent analysis of CTCs. Here, we present a device for the viable isolation and efficient retrieval of CTCs using slanted slot filters, formed by a reversibly deformable membrane barrier. Conventional filters have difficulties in retrieving captured cells, since they easily clog the slots. Moreover, large stress concentration at the sharp edges of squared slots, causes cell lysis. In contrast, the present device shows over 94% of high retrieval efficiency, since the slots can be opened simply by relieving the pressure. Furthermore, the inflated membrane barrier naturally forms the slanted slots, thus reducing the cell damage. By using cancer cell lines, we verified that the present device successfully isolate targeted cells, even at an extremely low concentrations ( 10 cells/0.1 ml). In the clinical study, 85.7% of patients initially showed CTC positive while the numbers generally decreased after the surgery. We have also proved that the number of CTCs were highly correlated with tumour invasiveness. Therefore, the present device has potential for use in cancer diagnosis, surgical validation, and invasiveness analysis.